AB0590 A validation study of the pregnancy morbidity questionnaire(PMQ) in women with antiphospholipid antibodies and pregnancy morbidity. (12th June 2018) - Schreiber, K.; Koder, S.; Ay, C.; Pabinger, I.; Jacobsen, S.
Abstract : Background: The presence of antiphospholipid antibodies (aPL) are associated with pregnancy complications. There is a lack of validated pregnancy questionnaires to assess previous pregnancy morbidity reliably in aPL positive patients. We therefore designed the pregnancy morbidity questionnaire (PMQ). Objectives: To validate the pregnancy morbidity questionnaire (PMQ) in the prospective Vienna Lupus Anticoagulant and Thrombosis Study (LATS) cohort. Methods: The Vienna Lupus Anticoagulant and Thrombosis Study (LATS) is an ongoing, single-centre, biobank-based, prospective observational cohort study enrolling patients (age >18 years) who are persistently positive for lupus anticoagulant (LA) (two positive tests at least 12 weeks apart) with or without a history of thrombosis or pregnancy complications 1 . The cohort currently consists of 150 patients (mean age: 41.3 years, female gender: n = 122 (81.3%), history of thrombosis or pregnancy complications: n = 111 (74.0%)). Of these 150 women, 15 were approached at their follow up visit and invited to fill out the PMQ. The PMQ consists eight questions outlined in table 2. Results: Twelve women agreed to participate, of whom nine had a previous history of pregnancy and/or pregnancy complications. Patient characteristics are shown in table 2. PMQ results are outlined in table 2. Conclusions: Our aim was to validate the PMQ in the prospective Vienna Lupus Anticoagulant and Thrombosis Study (LATS) cohort. Patients were able to recall their pregnancy history in great detail over a period of more than three decades. Our PMQ may provide a tool to assess previous pregnancy morbidity in patients with antiphospholipid antibodies. References: [1] Gebhart, J. P., F.; Koder, S.; Perkmann, T.; Quehenberger, P.; Zoghlami, C.; Ay, C.; Pabinger, I. Increased mortality in patients with the lupus anticoagulant: the Vienna Lupus Anticoagulant and Thrombosis Study (LATS). Blood125, 3477–3483. http://dx.doi.org/10.1182/blood-2014-11-611129 (2015). Disclosure of Interest: None declared